The Role of Society in Increasing Voter Participation in Pilkada in Kab. Deli Serdang - Prayoga, Boby Indra; Situmeang, Mahyudin; Azhari, El (Proceedings of International Conference of Graduate School on Sustainability, 2017)
The participation of the community in increasing voter participation in theelection of regional head elected by regional head election, can be considered orviewed as social problem in society, of course, the social problem has its owncause for the society itself.